Notes on Zethini (Hymenoptera, Vespidae, Eumeninae): complementary sex descriptions, synonymies and a new species of Zethus Fabricius - Lopes, Rogério Botion; Cruciol, Ana Helena; Noll, Fernando Barbosa (Zootaxa, 2020)
This paper brings a series of contributions to the taxonomy of the Zethini: description of a new species, Zethus denticlypeus Lopes, sp. n.; description of the female of Z. anomalus Cooper, 1999; description of the males of Z. angustior Bohart & Stange, 1965, Z. clypeolaris Bohart & Stange, 1965, Z. satanicus Bohart & Stange, 1965 and Argentozethus willinki Stange, 1979; synonymy of Discoelius argentinus Brèthes, 1905 under Z. dicomboda Spinola, 1851; and rearrangements for the species of Raphiglossoides Giordani Soika, 1936, with Raphiglossoides minutus (Gusenleitner, 2000) (= R. aethiopicus Giordani Soika, 1936) and R. gibbus (Gusenletiner, 2000) n. comb.